1984
DOI: 10.1159/000183245
|View full text |Cite
|
Sign up to set email alerts
|

Acquired Renal Cystic Disease in Renal Transplant Recipients

Abstract: End-stage kidneys are known to undergo cystic transformation in patients treated with long-term hemodialysis. Little has been published, however, on the occurrence of acquired renal cystic disease (ACD) in renal transplant recipients. The available clinical and histopathological data were gathered on 22 renal transplant recipients who had undergone either necropsy or nephrectomy. None of our patients exhibited cystic changes in their donor kidneys. However, 11 patients (50%) had ACD of the native kidneys while… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

1987
1987
1998
1998

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(16 citation statements)
references
References 7 publications
1
15
0
Order By: Relevance
“…The overall incidence of cysts in these groups (36.1 and 42.6%) was compatible with previous reports Years after renal transplantation [3][4][5]12] which investigated more than 22 transplant recipients. This incidence (36-43%) or renal cysts in transplant recipients with good graft function is much higher than that (0-7%) for the general population in the same age groups of 20-40 years [13,14].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The overall incidence of cysts in these groups (36.1 and 42.6%) was compatible with previous reports Years after renal transplantation [3][4][5]12] which investigated more than 22 transplant recipients. This incidence (36-43%) or renal cysts in transplant recipients with good graft function is much higher than that (0-7%) for the general population in the same age groups of 20-40 years [13,14].…”
Section: Discussionsupporting
confidence: 91%
“…Vaziri et al [3] reported a 50% rate of acquired cysts in their 22 autopsy or nephrectomy cases. Bommer et al [15], Mickisch et al [16] and Krempien et al [17] also reported the high incidences (75-100%) of cysts in the native kidney after renal transplantation in studies of 2-9 patients.…”
Section: Discussionmentioning
confidence: 98%
“…ACKD may regress after successful renal transplantation, and early renal transplantation in ESRD patients may prevent or impede the development of ACKD [15,16]. However, ACKD occurs in native kidneys following successful renal transplantation as in case 2 [17,18].…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of acquired cystic disease in hemodi alysis, CAPD and transplant patients is 35.2-79.3 [2,4,5,7,28], 29-54 [11,12] and 37-50% [17,34], respectively. These prevalence rates are derived from a number of studies with varying numbers of patients and durations of dialysis and recovery from transplantation; at first glance, there is apparently no significant difference among the three therapeutic modalities.…”
Section: Acquired Renal Cystic Disease In Patients On Dialysis or Witmentioning
confidence: 99%
“…Such levels of interest are also demonstra ted by many clinicians and nephrologists because of the reported high incidence of complications -renal tumors and retroperitoneal bleeding -associated with acquired renal cysts [2][3][4][5][6][7][8][9]. Over the last 10 years, the natural history of acquired renal cystic disease has become clearer [10] and, more recently, its relationship to continuous ambu latory peritoneal dialysis [9,[11][12][13][14][15][16] or renal transplanta tion [17][18][19][20][21][22][23] has been investigated. However, there is some dispute concerning what method and frequency of screening should be used for the early detection of renal cell carcinoma in dialysis patients, since some authors [7,9,[24][25][26] remain skeptical of the high incidences of this cancer among such patients.…”
mentioning
confidence: 99%